2006
DOI: 10.1111/j.1398-9995.2006.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of sublingual immunotherapy with tree pollen extract in children

Abstract: SLIT with tree pollen extract provided dose-dependent benefits in tree pollen-allergic children in terms of significantly reduced symptoms and medication use. The treatment was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 33 publications
(38 reference statements)
3
111
1
3
Order By: Relevance
“…25,28 Five studies demonstrated significant improvement in rhinitis/ rhinoconjunctivitis scores with SLIT, compared with placebo, with moderate to strong magnitudes of effect. 33,34,[36][37][38] Four studies did not show significant improvement with SLIT, 25,26,29,32 and 1 of these favored placebo. 26 The strength of evidence is moderate that SLIT improves rhinitis symptoms.…”
Section: Rhinitismentioning
confidence: 99%
See 2 more Smart Citations
“…25,28 Five studies demonstrated significant improvement in rhinitis/ rhinoconjunctivitis scores with SLIT, compared with placebo, with moderate to strong magnitudes of effect. 33,34,[36][37][38] Four studies did not show significant improvement with SLIT, 25,26,29,32 and 1 of these favored placebo. 26 The strength of evidence is moderate that SLIT improves rhinitis symptoms.…”
Section: Rhinitismentioning
confidence: 99%
“…[25][26][27][28][29][32][33][34][35][36][37][38] One-half of the studies evaluated dust mite allergens. 25,26,[32][33][34]38 Risk of bias was low in 4 studies, 27,29,32,34 medium in 6 studies, 26,33,[35][36][37][38] and high in 2 studies. 25,28 Five studies demonstrated significant improvement in rhinitis/ rhinoconjunctivitis scores with SLIT, compared with placebo, with moderate to strong magnitudes of effect.…”
Section: Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of SLIT courses varied from 3 months (minimum duration) to 3 years (maximum duration). The administration regimen was preseasonal in three studies (27,32,44), co-seasonal in three (15,42,47), and continuous in eight trials (30,35,38,39,41,43,46,54), despite the allergen was seasonal. In the remaining 27 trials the adopted regimen was precoseasonal.…”
Section: Literature Analysismentioning
confidence: 99%
“…Eighteen months of SLIT with tree pollen extract provided dose-dependent benefits in terms of significantly reduced symptoms and medication use. (Valovirta E et al, 2006) Two adequately powered, well-designed double blind placebo controlled (DBPC) www.intechopen.com randomized controlled trial (RCTs) have now been published, both showing a clear effect of allergen tablets in childhood. A statistically significant reduction in rhinitis symptoms (28%) and medication (64%) score was shown during the pollen season in 114 children receiving active grass allergen tablets (with 15g Phl p 5) compared with 120 children in the placebo group.…”
Section: Clinical Efficacymentioning
confidence: 99%